Application Of User Centered Design (Ucd) Method For Ui/Ux Design At Husqy Petshop - Herlambang Cahya Pratama, Yudha; Al Hafidz, Mohammad; Lazuardy, Nouval; Naristi, Keysa (PT. Hafasy Dwi Nawasena, 2024)
The era of digital transformation has made the MSME industry in Indonesia become technology literate, one of which is Husqy Petshop. Husqy Petshop is transforming by creating e-commerce which makes transaction accessibility easier. The development of the Husqy Petshop e-commerce application must pay attention to the right User Interface (UI) and User Experience (UX) so that it can be used by users comfortably. User Interface (UI) and User Experience (UX) are two important aspects of application design that play a role in the interaction between users and products. Good UI/UX design is obtained by using a method that takes into account the appearance and user experience, one of which is User Centered Design (UCD). The Husqy Petshop application, which applies the User Centered Design (UCD) method, does not only focus on technical aspects, but also considers user needs, preferences and experience. The test results using the Single Ease Question (SEQ) method produced an average score of 6.89 which states that the appearance of the Husqy Petshop Application is easy to use.The aim of this research is to provide recommendations for interface designs that suit the needs and are easy for users to use.